Functional relevance of naturally occurring mutations in adhesion G protein-coupled receptor ADGRD1 (GPR133). (December 2016) - Fischer, Liane; Wilde, Caroline; Schöneberg, Torsten; Liebscher, Ines
Abstract Background A large number of human inherited and acquired diseases and phenotypes are caused by mutations in G protein-coupled receptors (GPCR). Genome-wide association studies (GWAS) have shown that variations in theADGRD1 (GPR133 ) locus are linked with differences in metabolism, human height and heart frequency. ADGRD1 is a Gs protein-coupled receptor belonging to the class of adhesion GPCRs. Results Analysis of more than 1000 sequenced human genomes revealed approximately 9000 single nucleotide polymorphisms (SNPs) in the humanADGRD1 as listed in public data bases. Approximately 2.4 % of these SNPs are located in exons resulting in 129 non-synonymous SNPs (nsSNPs) at 119 positions ofADGRD1 . However, the functional relevance of those variants is unknown. In-depth characterization of these amino acid changes revealed several nsSNPs (A448D, Q600stop, C632fs [frame shift], A761E, N795K) causing full or partial loss of receptor function, while one nsSNP (F383S) significantly increased basal activity of ADGRD1. Conclusion Our results show that a broad spectrum of functionally relevantADGRD1 variants is present in the human population which may cause clinically relevant phenotypes, while being compatible with life when heterozygous.